Association between serum uric acid levels and cerebral white matter lesions in Chinese individuals. (1st December 2016) - Sun, Meng-Jiao; Li, Bing-Hu; Long, Chun-Yan; Wang, Yan-Qin; Zhou, Yi; Liu, Yun; Liao, Shao-Qiong; Pi, Yan; Guo, Lu; Zhang, Li-Li; Li, Jing-Cheng
Abstract : Purpose/aim of the study : We aimed to evaluate the association between serum uric acid (SUA) levels and cerebral white matter lesions (WMLs) in Chinese individuals. Material and methods : We prospectively identified patients aged 50 years and older in neurology department from July 2014 to March 2015. Both periventricular WMLs (P-WMLs) and deep WMLs (D-WMLs) were identified on magnetic resonance imanging (MRI) scans and the severity was graded using the Fazekas method. Multivariate logistic regression analyses were performed to examine the association between SUA and WMLs. Results : A total of 480 eligible participants were enrolled in this study. SUA level in severe group was much higher than that in mild group (for P-WMLs: 320.21 ± 79.97 vs. 286.29 ± 70.18, p = 0.000; for D-WMLs: 314.71 ± 74.74 vs. 290.07 ± 74.04, p = 0.031). Subgroup analyses showed that higher SUA level was associated with higher severity of P-WMLs in women, but not in male patients. Multivariate logistic regression analyses showed that SUA was still associated with increased risk of higher severity of P-WMLs (OR = 1.003, 95% = 1.000–1.006), but not D-WMLs. Conclusion : Elevated SUA level was independently associated with greater odds of higher severity of P-WMLs, particularly in women.